PENGARUH KEUNIKAN PRODUK DAN MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PRODUK TAS KULIT ASLI KOESOEMA BAGS DENGAN KEPERCAYAAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Septina Nurmalita Putri Kusuma Wardani; Muinah Fadhilah; Ambar Lukitaningsih (Universitas Sarjanawiyata Tamansiswa, 2026)
This research is motivated by the intense competition in the leather fashion industry, which demands product differentiation strategies. This study aims to analyze the influence of product uniqueness and social media on purchasing decisions, with consumer trust as an intervening variable, at Koesoema Bags. Using a quantitative approach, data was collected through a survey of 172 respondents selected using a purposive sampling technique. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results indicate that product uniqueness and social media have a positive and significant influence on purchasing decisions and consumer trust. Another key finding demonstrates that consumer trust plays a significant role in mediating the relationship between product uniqueness and social media on purchasing decisions. The implications of this study emphasize the importance of maintaining personalized (custom) services and authentic digital interactions to build trust and drive sales of local products.